2021
DOI: 10.1111/vde.13044
|View full text |Cite
|
Sign up to set email alerts
|

Altered plasma cytokines in dogs with atopic dermatitis

Abstract: Background Canine (Canis lupus familiaris) atopic dermatitis (AD) shares similar clinical signs to human AD. The abnormal immune response of AD is orchestrated by T lymphocytes, and may include variable involvement of cytokines, regulatory T (Treg) cells, eosinophils, mast cells and other immune components. Helper T (Th)2 cytokines often predominate initially, followed by Th1 cytokines in more chronic phases. Hypothesis/Objectives Pro‐inflammatory and Treg cytokines have been shown to play a role in human AD, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 73 publications
(189 reference statements)
1
19
1
Order By: Relevance
“…IL-8 was found to be over-expressed in conjunctiva and tears of atopic dogs despite subtle conjunctival symptoms [ 30 ]. Finally, a recent study showed that the plasma concentrations of IL-8, IL-7, and IL-15 cytokines were elevated in canine AD patients compared to in control dogs [ 31 ]. In our study, the correlation between IL-8 content and otitis severity (OTIS3 score) was weak, possibly due to the low number of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…IL-8 was found to be over-expressed in conjunctiva and tears of atopic dogs despite subtle conjunctival symptoms [ 30 ]. Finally, a recent study showed that the plasma concentrations of IL-8, IL-7, and IL-15 cytokines were elevated in canine AD patients compared to in control dogs [ 31 ]. In our study, the correlation between IL-8 content and otitis severity (OTIS3 score) was weak, possibly due to the low number of dogs.…”
Section: Discussionmentioning
confidence: 99%
“…37 Of the remaining studies, four showed no difference, and one showed reduced, although not significantly, protein and mRNA levels of IFNγ in the blood (sera, plasma and PBMCs). [38][39][40][41]90 The mRNA expression of IFNγ also was unchanged after HDM challenge in the acute skin lesions or primary keratinocytes collected from the cAD model, 21,91 whereas its mRNA expression was significantly increased in PBMCs collected from dogs of a similar AD model. 12 A study of dogs treated with oclacitinib showed that IFNγ production by peripheral blood CD4 + and CD8 + T cells was significantly reduced on Day (D)240 and D300 after the initiation of treatment yet returned to baseline levels on D360 without an associated clinical relapse.…”
Section: Interferonγmentioning
confidence: 98%
“…12,21,37 By contrast, four other studies on sera from client-owned dogs did not find a difference in the concentration of IL-4 between dogs with AD and healthy controls. [38][39][40][41] Since the HDMinduced experimental AD model represents the earliest stages of acute flares of AD and most client-owned dogs have more chronic lesions, it is possible that IL-4 only plays an important role during the induction or acute phase of cAD. Furthermore, it is interesting to note that the percentage of IL-4-producing T cells in dogs with AD did not change after one year of treatment with oclacitinib, despite the clinical improvement, 42 which indicates that IL-4 might be a less important inflammatory cytokine in chronic cAD.…”
Section: Interleukin-4mentioning
confidence: 99%
See 2 more Smart Citations